2001
DOI: 10.1042/0264-6021:3590517
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(4,5)P2 and phospholipase C-independent Ins(1,4,5)P3 signals induced by a nitrogen source in nitrogen-starved yeast cells

Abstract: Addition of ammonium sulphate to nitrogen-depleted yeast cells resulted in a transient increase in Ins(1,4,5)P(3), with a maximum concentration reached after 7-8 min, as determined by radioligand assay and confirmed by chromatography. Surprisingly, the transient increase in Ins(1,4,5)P(3) did not trigger an increase in the concentration of intracellular calcium, as determined in vivo using the aequorin method. Similar Ins(1,4,5)P(3) signals were also observed in wild-type cells treated with the phospholipase C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…N. crassa PLC is thought to be activated by membrane stretch, generating IP 3 , which triggers Ca 2ϩ release from hyphal tip vesicles, thus maintaining a high Ca 2ϩ concentration required for hyphal tip growth (6). In S. cerevisiae, however, transient IP 3 increase in nitrogen-depleted cells following addition of ammonium sulfate did not trigger a spike in intracellular calcium (7). In glucose-starved S. cerevisiae, glucose addition caused PLC-dependent influx of extracellular calcium accompanied by a transient increase in IP 3 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…N. crassa PLC is thought to be activated by membrane stretch, generating IP 3 , which triggers Ca 2ϩ release from hyphal tip vesicles, thus maintaining a high Ca 2ϩ concentration required for hyphal tip growth (6). In S. cerevisiae, however, transient IP 3 increase in nitrogen-depleted cells following addition of ammonium sulfate did not trigger a spike in intracellular calcium (7). In glucose-starved S. cerevisiae, glucose addition caused PLC-dependent influx of extracellular calcium accompanied by a transient increase in IP 3 .…”
mentioning
confidence: 95%
“…C. neoformans cultures grown overnight in YPD broth were pelleted, resuspended in water to an optical density at 600 nm (OD 600 ) of 10, spotted onto YPD plates, and incubated overnight at 30°C. Forty to 80 mg of cryptococcal cells was scraped from the plates, weighed, quenched by adding 4 ml of ice-cold (ϽϪ20°C) 60% methanol, and vortexed vigorously (7,9). Quenched cells were pelleted by centrifugation and resuspended in ice-cold 4% perchloric acid (1 ml per 75 mg cells).…”
Section: Methodsmentioning
confidence: 99%
“…It was suggested that glucose re-admission might provoke phosphoinositide turnover and activate a plasma membrane H ϩ pump, with Plc1p needed for both responses (25), but again deacylation may have caused much of the observed phosphoinositide loss. Nitrogen re-addition to nitrogen-starved yeast provokes rapid Ins(1,4,5)P 3 formation (26), but this seems not to need Plc1p (27). Hypo-osmotic shock evokes a [Ca 2ϩ ] i rise in yeast (28) and in some animal and plant cells, and hypo-osmotic shock may sometimes activate PIC (29,30).…”
mentioning
confidence: 99%